A PILOT EXTERNAL QUALITY ASSURANCE STUDY OF TRANSFUSION SCREENING FOR HIV, HCV AND HBSAG IN TWELVE AFRICAN COUNTRIES - Bloch, Evan M (2014)
BACKGROUND AND OBJECTIVES: Serologic screening for the major transfusion transmissible viruses (TTV) is critical to blood safety and has been widely implemented. However, actual performance as measured by proficiency testing has not been well studied in Sub-Saharan Africa. Therefore, we conducted an external quality assessment of laboratories engaged in transfusion screening in the region. MATERIALS AND METHODS: Blinded test panels, each comprising 25 serum samples that were pedigreed for HIV, HBsAg, HCV and negative status, were sent to participating laboratories. The panels were tested using the laboratories’ routine donor screening methods and conditions. Sensitivity and specificity were calculated and multivariable analysis was used to compare performance against mode of testing, country and infrastructure. RESULTS: A total of 12 African countries and 44 laboratories participated in the study. The mean (range) sensitivities for HIV, HBsAg and HCV were 91.9% (14.3-100), 86.7% (42.9-100) and 90.1% (50-100), respectively. Mean specificities for HIV, HBsAg and HCV were 97.7%, 97% and 99.5% respectively. After adjusting for country and infrastructure, rapid tests had significantly lower sensitivity than enzyme immunoassays (EIA) for both HBsAg (p<0.0001) and HCV (p<0.05). Sensitivity also varied by country and selected infrastructure variables. CONCLUSION: While specificity was high, sensitivity was more variable and deficient in a substantial number of testing laboratories. These findings underscore the importance of proficiency testing and quality control, particularly in Africa where TTV prevalence is high.